(untitled) (Research, Society and Development, 2021)
This article analyses how a group of bank employees working at an agency in Mariana – MG grants meaning to pleasure and suffering at work using the Word Evocation Test (TEP). Research participants were invited to evoke a set of words through two inducing expressions following a qualitative perspective. Furthermore, participants were asked to discuss and explain the terms already listed. Even following the utilitarian view concerning the meaning of pleasure at work, the results reinforce the presence of dynamics of suffering in the workplace. Working in the banking sector has revealed some contradictions related to professional satisfaction, supporting recent studies. Accordingly, this article contributes to the field and presents a research agenda to further investigations deemed necessary on pleasure and suffering at work, thus broadening the discussion.